2021
DOI: 10.1016/j.heliyon.2021.e07227
|View full text |Cite
|
Sign up to set email alerts
|

Ternary and quaternary blends as partial replacement of cement to produce hollow sandcrete blocks

Abstract: Hollow sandcrete blocks constitute more than 90% of residential building construction in developing countries especially in West Africa. Over-reliance on dredged river sands and conventional ordinary Portland cement (OPC) contributes to environmental degradation and post-construction problems such as swelling and shrinkage-induced cracks prevalent in construction projects. The study investigates potential utilization of locally available materials such as laterite, calcite and calcined clay as ternary and quat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Each sample was heated from room temperature to 100 • C at 10 • C/min, kept at 100 • C for 30 min and then heated to 1000 • C at 10 • C/min. The chemically bound water was calculated using Equation (10) while the calcium hydroxide content was calculated using Equations ( 11) and (12). In all ten calculations, the losses of clay and stone powder were compensated for by subtracting their corresponding values as shown in Equations (S1), (S8) and (S9) (refer to Data Availability Statement).…”
Section: Amorphous Silica Concentration Measurement Via Naoh Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample was heated from room temperature to 100 • C at 10 • C/min, kept at 100 • C for 30 min and then heated to 1000 • C at 10 • C/min. The chemically bound water was calculated using Equation (10) while the calcium hydroxide content was calculated using Equations ( 11) and (12). In all ten calculations, the losses of clay and stone powder were compensated for by subtracting their corresponding values as shown in Equations (S1), (S8) and (S9) (refer to Data Availability Statement).…”
Section: Amorphous Silica Concentration Measurement Via Naoh Digestionmentioning
confidence: 99%
“…The particle size of stone powder and mineralogical origin of the parent rock, such as granite, limestone or basalt, determines its reusability in construction materials. For example, coarse sizes (>75 µm) are reused in concrete [10,11] or mortar [8] or sandcrete blocks [12], while fine sizes (<75 µm) are used as partial cement replacements [7,13,14] or included in roof tiles [15]. In these studies, either the durability [5,13] or the strength of concrete [10,11], mortar [8] or tiles [15] was enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting concrete had two key characteristics: slump flow and compressive strength. According to the study's findings, the optimization process determined that the optimal values for the input factors, LP, PET, and SP, were 20.1%, 2.4%, and 1.16% by weight, respectively [ 29 ]. explores using locally accessible materials like laterite, calcite, and calcined clay as blends to replace cement and quarry dust as 100% river sand replacement using the Taguchi-Response surface technique.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of these experiments revealed that by including these materials as elements, the quality of blocks and bricks may be conserved. Additionally, research analyses have shown that pozzolanic recycled materials, including metakaolin, waste glass, ceramic and tile wastes, sawdust, fly ash, sewage sludge ash, rice husk, and clay brick, can be utilized as substitutes for cement to produce high-quality blocks and bricks for building [15] [16] [17] [18]. Studies are also examining ways to supply inexpensive or reasonable construction materials for homes without sacrificing their worth, as well as how to help create a sustainable, neat ecosystem by reclaiming these unwanted items.…”
Section: Introductionmentioning
confidence: 99%